Knowledge of coronary heart disease risk factors and associated dietary fat intake among medical students - Hansaro Andika Zalukhu; Haddiyya Wardhani Nugroho; Hanandhito Satya Pradhipta; Ratna Sari Wijaya (Fakultas Kedokteran Universitas Pelita Harapan, 2025)
Background: Coronary heart disease (CHD) prevalence has increased among young adults. The most common CHD risk factor among young adults was high daily fat intake. Knowledge regarding CHD risk factors was a crucial element in determining health behaviour, including healthy dietary patterns. However, the level of CHD knowledge and its association with dietary fat intake among medical students is still unclear. Methods: The study was performed among preclinical medical students at the Pelita Harapan University, Indonesia. The CHD risk factor knowledge was assessed using the validated Heart Disease Fact Questionnaire (HDFQ), comprising of 25 items. The dietary fat intake was evaluated using the validated Block Dietary Fat Screener (BDFS) questionnaire. Results: A total of 98 participants were included in this study. The median age of the participants was 19 years (IQR 18-20). Of the 98 participants, 71 (72%) participants had adequate knowledge of CHD risk factors. Older age, being female, and being in the third year of medical study were related to higher HDFQ scores. The daily fat intake was classified as high in 33 (34%) of participants and very high in 33 (34%) of participants. No significant difference in dietary fat intake level was observed between participants with and without adequate knowledge of CHD risk factors. Conclusion: This study reveals that most medical students had adequate knowledge of CHD risk factors. However, the knowledge factor did not lead to healthy dietary pattern adoption among medical students, suggesting that the implementation of an education and training program to motivate lifestyle modification was required.